2017
DOI: 10.1111/gcb.13675
|View full text |Cite
|
Sign up to set email alerts
|

Responses of belowground communities to large aboveground herbivores: Meta‐analysis reveals biome‐dependent patterns and critical research gaps

Abstract: The importance of herbivore-plant and soil biota-plant interactions in terrestrial ecosystems is amply recognized, but the effects of aboveground herbivores on soil biota remain challenging to predict. To find global patterns in belowground responses to vertebrate herbivores, we performed a meta-analysis of studies that had measured abundance or activity of soil organisms inside and outside field exclosures (areas that excluded herbivores). Responses were often controlled by climate, ecosystem type, and domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 80 publications
7
102
0
Order By: Relevance
“…Thus, we argue that if insect herbivory is to be included into the conceptual framework for understanding ecosystem consequences of herbivores, additional modifications are needed, particularly in terms of temporal variability. Finally, Andriuzzi and Wall (2017) highlight the need for herbivory studies outside grassland ecosystems, which is also strongly relevant based on our results from a N poor forest ecosystem.…”
Section: Ecosystem Impacts Of Insect Litter Transformationmentioning
confidence: 61%
See 1 more Smart Citation
“…Thus, we argue that if insect herbivory is to be included into the conceptual framework for understanding ecosystem consequences of herbivores, additional modifications are needed, particularly in terms of temporal variability. Finally, Andriuzzi and Wall (2017) highlight the need for herbivory studies outside grassland ecosystems, which is also strongly relevant based on our results from a N poor forest ecosystem.…”
Section: Ecosystem Impacts Of Insect Litter Transformationmentioning
confidence: 61%
“…The complex relationship between C and N mineralisation we found in this study (and others before) challenges the first assumption. The recent review of belowground consequences of vertebrate herbivory by Andriuzzi and Wall (2017) challenges the second assumption, as herbivore types were found to be equally or more important than trophic effects for predicting soil process rates and ecological responses, particularly due to physical soil disturbance. Insect herbivores do not physically influence their environment to the same extent as vertebrates, but they tend to show larger variation in abundances (i.e.…”
Section: Ecosystem Impacts Of Insect Litter Transformationmentioning
confidence: 99%
“…Moreover, ungulate trampling in semi‐arid conditions has less pronounced effects than on wet soils (Drewry, ; Schrama et al., ). As physical disturbance by large herbivores often decreases soil animal and microbial abundance (Andriuzzi & Wall, ), future studies should test whether it can override resource‐related effects on body size depending on climate and soil physical conditions. Presumably, pore space is especially important for large nematodes, the responses of which may be difficult to isolate with traditional mean‐based statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Mills and Adl () found that mean nematode length increased in time under cattle grazing in a sandy loam. Overall, while much progress has been made in understanding how herbivores affect the abundance of other animals (Andriuzzi & Wall, ; Daskin & Pringle, ; Vandegehuchte, Schütz, de Schaetzen, & Risch, ), their effects on functional traits are under‐studied, and body size is no exception.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous additional external drivers of PSF that are beyond the scope of this paper (Box ). However, the factors examined in detail here are known drivers of plant and soil organism performance and the ecosystem processes (e.g., nutrient cycling, productivity, carbon sequestration) they drive and hence would be expected to be important drivers of PSFs (Andriuzzi & Wall, ; Blankinship, Niklaus, & Hungate, ; Smith‐Ramesh & Reynolds, ). We selected these drivers because they are ubiquitous across ecosystems and are strongly associated with pressing ecological concerns (e.g., climate change, sustainable management of soils, trophic cascades), and the substantial research conducted to date allowed us to make robust predictions about how they might drive PSFs under different scenarios.…”
Section: The Importance Of Plant–soil Feedbacks and Critical Knowledgmentioning
confidence: 99%